An Analysis of the Higher Order Thinking Skills (HOTS) in the National Examination of English On Junior High School Level - Astuti Widiyaningsih; Tri Ilma Septiana (IAIN Syekh Nurjati Cirebon, 2019)
This study was carried out to obtain empirical evidences on the distribution of the higher order thinking skills (HOTS) based on the revised edition of Bloom’s Taxonomy in the National Examination of English subject on Junior High School level. This study used document analysis method that enables the writers to identify, analyze, and categorize the quality of National Examination questions into Bloom’s taxonomy. the writers employed questions from 2016-2017 and 2017-2018 academic years as sample. The major findings of this study demonstrate that they were only 6 and 9 out of 50 questions or 12% and 18% from two respective National Examinations can be categorized into the higher order thinking skills. Moreover, the writers also found that the highest order thinking skills classified into C4 or analysis ability. Meanwhile, the lower order thinking skills can be found as many as 44 and 41 questions or 88% and 82% from respective each academic year. In conclusion, the writers conclude that the most questions of National Examination in Junior High School Level can be categorized into the Lower Order Thinking Skills (LOTS). Besides, based on the data the improvement quality of questions was only 6% from two academic years.